Materiell og profesjonell stigmatisering av mennesker med sykelig overvekt - Christiansen, Wenche Skeivoll; Karlsen, Tor-Ivar; Larsen, Inger Beate (Nordisk tidsskrift for helseforskning, 2017)
The aim of this study is to show how people suffering from severe obesity might experience stigmatization. We interviewed 6 persons recruited from a Norwegian rehabilitation center, specialized in lifestyle intervention in severe obesity. We found that the participants suffering from severe obese experienced stigmatization and thus felt that they a) did not fit into the materiel world and b) experienced a lack of respect from health care professionals. The results are discussed according to how contemporary symbols are embedded in our surroundings and in our bodies. The conclusion underlines severe obesity as a complex problem which is strengthened by rooms and interior designed for ideal sizes. The prejudices that health care professionals express worsen these patients feeling of stigma. We refer to this as material and professional stigmatization.